2007
DOI: 10.1016/j.expneurol.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency impairs re-injury induced reversal of neuronal atrophy: Relation to T cell subsets and microglia

Abstract: Following facial nerve resection in the mouse, a substantial number of neurons reside in an atrophied state (characterized by cell shrinkage and decreased ability to uptake Nissl stain), which can be reversed by re-injury. The mechanisms mediating the reversal of neuronal atrophy remain unclear. Although T cells have been shown to prevent neuronal loss following peripheral nerve injury, it was unknown whether T cells play a role in mediating the reversal of axotomy-induced neuronal atrophy. Thus, we used a fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…As statistical analysis revealed that the distribution of the data was not normal, Spearman's rank correlation analysis was used to determine the relationship between T cells and neuronal death (as measured by the number of microglial phagocytic clusters). For neuronal cell counts, facial motor neurons were quantified in 8 representative sections of the FMN, as described previously (Deboy et al, 2006;Ha et al, 2007a). The medial nucleus, which receives innervation from the auricular branch of the facial nerve, remained uninjured and thus was excluded from the analysis.…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…As statistical analysis revealed that the distribution of the data was not normal, Spearman's rank correlation analysis was used to determine the relationship between T cells and neuronal death (as measured by the number of microglial phagocytic clusters). For neuronal cell counts, facial motor neurons were quantified in 8 representative sections of the FMN, as described previously (Deboy et al, 2006;Ha et al, 2007a). The medial nucleus, which receives innervation from the auricular branch of the facial nerve, remained uninjured and thus was excluded from the analysis.…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…Furthermore, PACAP mRNA is expressed by injured mouse FMN after facial nerve axotomy (Armstrong et al ., 2003) and PACAP increases Th2-associated chemokine expression in cultured murine microglia (Wainwright et al ., 2008). Since CD4 + T cells are present in the facial motor nucleus after injury (Ha et al ., 2007) and the Th2, but not the Th1, effector subset mediates FMN survival (Deboy et al ., 2006), we hypothesized that Th2-associated chemokines would be expressed in the facial motor nucleus after facial nerve axotomy. To delineate this mechanism, we studied the expression of Th2-associated chemokine, CCL11, and Th1-associated chemokine, CXCL11, in the facial motor nucleus after facial nerve axotomy.…”
Section: Discussionmentioning
confidence: 99%
“…After facial nerve axotomy, the number of astrocytes in the facial motor nucleus that were immunoreactive for CCL11 increased significantly at time points consistent with significant T cell infiltration (Raivich et al ., 1998; Ha et al ., 2007). There is a growing literature demonstrating chemokine expression by astrocytes as a result of neuronal injury (Katayama et al ., 2009; Khorooshi et al ., 2008; Babcock et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinjuring the facial nerve stimulates a reversal in the atrophic status of the injured neurons, causing an increase in both their size and number [7]. As described below, data from our research suggests that under normal physiological conditions, the reversal of atrophy and the ability of reinjured facial motor neurons to regain their normal phenotype is dependent on a normal functioning cellular immune system [8,9]. To our knowledge, this is the only model of neuronal atrophy reversal that has been studied in the context of immunity or linked to immune function.…”
Section: Atrophied Neurons Have the Potential To Regenerate Their Phementioning
confidence: 99%